Evolution of the quadrupole hyperfine interaction while milling a Si-HfO2? blend Original Research Article - Chain, Cecilia Yamil (2012)
As HfO2 appears as a good candidate to replace SiO2 in Si complementary metal-oxide-semiconductor devices, a refined knowledge of the possible solid-state reactions between Si and HfO2 is valuable. Being the Perturbed Angular Correlations technique a very sensitive method to detect small changes in solid state, the goal of this work is to follow the different stages that occur while ball milling a blend Si-HfO2 by inspecting the hyperfine quadrupole interaction at Hf sites. The characterization is complemented by X-ray diffraction analysis. For comparison, a similar study on pure m-HfO2 is carried out. The results seem to reveal a gradual incorporation of Si in a tetragonal defective phase of hafnia with milling time. In addition, the formation of precursor arrays of the HfSiO4 structure takes place. After an annealing at 1000 °C an important amount of crystalline hafnon appears.